2021
DOI: 10.3390/ijerph18168758
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Effective and Safe Multidisciplinary Primary Care Teamwork: Using the Time of COVID-19 as a Case Study

Abstract: Effective medical teamwork can improve the effectiveness and experience of care for staff and patients, including safety. Healthcare organizations, and especially primary care clinics, have sought to improve medical teamwork through improved layout and design, moving staff into shared multidisciplinary team rooms. While co-locating staff has been shown to increase communication, successful designs balance four teamwork needs: face-to-face communications; situational awareness; heads-down work; perception of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
(75 reference statements)
0
12
0
1
Order By: Relevance
“…They also performed telehealth consultations from these rooms. Such separation provided physical isolation and distance to the providers; however, it hindered teamwork and communication with other team members due to a lack of situational awareness, as noted in a previous study (Lim et al, 2021).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…They also performed telehealth consultations from these rooms. Such separation provided physical isolation and distance to the providers; however, it hindered teamwork and communication with other team members due to a lack of situational awareness, as noted in a previous study (Lim et al, 2021).…”
Section: Resultsmentioning
confidence: 90%
“…Not surprisingly, a recent study confirmed that staff members' teamwork and communication experiences decreased during the pandemic in primary care clinics (Lim et al, 2021). For instance, providers in one clinic reported significantly lower communication scores in 2020 (3.01 + 0.10) compared to the prepandemic scores in 2017 (3.47 + 0.11).…”
Section: Physical Distancing Safety and Teamworkmentioning
confidence: 90%
See 2 more Smart Citations
“…The article of Lim et al (2021) [ 48 ] shows how changes and adaptations in the physical environment of healthcare, especially in primary care, have influenced communication, situational awareness, heads-down work, social support and activities, and asynchronous information exchanges. Using two case studies, they show how design changes can either improve or hinder teamwork.…”
Section: Discussionmentioning
confidence: 99%